The Effect of Operational Performance on Financial Performance of Companies Listed on the Indonesia Stock Exchange - Gusti Ayu Putu Rustika Pradnyani ; I Wayan Gde Wahyu Purna Anggara (E-Jurnal Akuntansi, 2025)
Financial performance reflects a company’s financial condition over a specific period and can be measured using profitability ratios. The profitability of companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period shows a fluctuating trend, indicating challenges in maintaining financial performance amid market dynamics. This study aims to analyze the effect of operational performance on financial performance. The research population consists of all companies listed on the IDX during the 2018–2023 period. The sample was selected using a random sampling method, resulting in 1,440 observations. The analytical tool employed in this study is panel data regression analysis with a Fixed Effect Model approach, processed using Stata software. The results indicate that operational performance, proxied by liquidity and company efficiency, has a positive effect on financial performance, proxied by profitability."